EFEKTIVITAS DAN EFISIENSI PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN SETELAH DIBERLAKUKANNYA UNDANG-UNDANG NOMOR 28 TAHUN 2009 DI KOTA SINGKAWANG - B01109043, BENI HANDOYO (Jurnal Curvanomic, 2015)
Application of Act No. 28 of 2009 on local taxes and levies, is expected to increase local revenues. One source of revenue has been handed over to the local government authority of the collection is the Tax on Acquisition of Land and Buildings. This study titled "effectiveness and efficiency of Customs Collection Acquisition of Land and Building after the enactment of Law No. 28 of 2009 in Singkawang", which aims to "identify and analyze the effectiveness and efficiency of collection BPHTB after the transfer of management authority to the area". The method used is the method of analysis of the effectiveness and efficiency which aims to see how effective and efficient when BPHTB tax has been run by the City of Singkawang. In the years 2008-2010 when he was managed by the central government, the effectiveness calculations show that the average value of its effectiveness by 108.66% with a very effective criteria and after the authority of the government of Singkawang (2011-2013) the average effectiveness of 112.25 % while the efficiency in 2008-2010 by an average of 26.55% and in 2011-2013 amounted to 26.48% with very efficient criteria. vKeywords: BPHTB, Effectiveness and Efficiency